Surgery of Undescended Testis by Scrotal Approach; Benefits and Limitations - salimi, amrollah; shahmoradi, ladan; vahedian, mostafa; moradi, alireza; Sharifi, Mohammadreza (Iranian Journal of Pediatric Surgery, 2024)
Background: The term of undescended testis refers to the cessation of the natural descending of the testis into the scrotum. Due to the advantages of the scrotal orchiopexy method over inguinal orchiopexy in some studies, we decided to conduct a similar study on children in Hazrat Masoumeh Hospital in Qom in 2016-2019 and we evaluated the effect of scrotal surgery in the treatment of UDT. Material and methods: In this study, among the files of children with palpable UDT between 2016-2019 who were undergone scrotal or inguinal surgery in Hazrat Masoumeh Hospital in Qom, the number of sample files from these files is selected and divided into two groups. One group was undergone traditional inguinal surgery and the other group were under scrotal surgery. Results: The mean operation time for type of incision above the scrotum and in the inguinal region were 8.27 ± 2.51 and 3.14 ± 12.08 minutes, respectively. The highest location in scrotal surgery was 70 (52.67%) in the external ring area and 101 (60.47%) was inguinal canal in inguinal surgery. In the scrotal method in no case and in the inguinal method only one case of secondary UDT was observed. In the scrotal method in no case and in the inguinal method only one case of wound infection was observed. Conclusion: Finally, our study showed that the scrotal method has more advantages than the inguinal method, the only limitation in this method is the location of the testis.